(untitled) - Yoshida, Yasuo ([Tokyo], 1976)
The book has the best sytyle to learn Grammar i have seen yet, THe book is old and vocabulary outdated, it refers to Russia and the USSR. You are given ample oppertunity to learn the grammer from each section and how to use it in everyday life. There is multipule dialogs that contian what you may need to say if you got to a resteraunt or hotel, ask for help, basic things.
Keywords: Japanese language; Textbooks for foreign speakers